Peptide‐Modulated pH Rhythms. Issue 16 (21st June 2022) - Liu, Mengfei; Yuan, Ling; Zhu, Chenghao; Pan, Changwei; Gao, Qingyu; Wang, Hongzhang; Cheng, Zhenfang; Epstein, Irving R.
Abstract: Many drugs adjust and/or control the spatiotemporal dynamics of periodic processes such as heartbeat, neuronal signaling and metabolism, often by interacting with proteins or oligopeptides. Here we use a quasi‐biocompatible, non‐equilibrium pH oscillatory system as a biomimetic biological clock to study the effect of pH‐responsive peptides on rhythm dynamics. The added peptides generate feedback that can lengthen or shorten the oscillatory period during which the peptides alternate between random coil and coiled‐coil conformations. This modulation of a chemical clock supports the notion that short peptide reagents may have utility as drugs to regulate human body clocks. Abstract : A non‐equilibrium pH oscillatory system, considered as a biomimetic rhythm, is used to study the effect of pH‐responsive peptides on dynamics. The successful modulation of oscillations by small peptides suggests that inorganic oscillators may be useful tools for studying drug‐induced regulation of biological rhythms and treatment of dynamical diseases.